Prioritizing the Main Elements of Quality Costs in Design-Build Mass-Housing Projects - Mohammad Balouchi; Majid Gholhaki; Ali Niousha (Civil Engineering Journal, 2019)
Reducing the cost of quality in mass-housing projects can reduce the overall cost and can also result in increasing profitability or the possibility of getting more projects due to the lower price offered in the tenders. The first step to reduce the cost of quality is to identify different elements, determine their impact on the final product quality and then prioritize them. In this study, questionnaires and structured interviews with experienced construction professionals were employed to identify and prioritize the fundamental elements using the P-A-F (prevention, evaluation, and failure) method, one of the most well-known methods for categorizing quality costs. The results indicate a high impact of preventive activities and the low impact of external failure activities on final product quality. According to the results, the use of experienced specialists and skilled workers is more effective than in-service training of inexperienced forces. Corrective actions of non-conformities and design improvements have a significant impact on final product quality. The new approach to COQ elements ranking, used in this research, can help decision-makers to prioritize the most effective activities in construction projects to increase final quality with an optimum quality cost.